ANALISIS RELASI SOSIAL PADA PETANI LEBAH MADU HUTAN DI SUSUN BATU RAWAN KECAMATAN SELIMBAU - Abang Hendra; Fatmawati Fatmawati; Imran Imran (Universitas Tanjungpura, 2019)
AbstractThe title of this research is analysis of social relations in “forest honey bee farmers in viilage Batu Rawan subdistrict Selimbau” A common problem in this study is how social relations of forest honey bee farmers in subdistrict Batu Rawan Selimbau district. With sub problem first How social relation of honeybee farmer forest in viilage Batu Rawan sub-district Selimbau in cooperation, second how social relations in honeybee Farmer forest in Batu Rawan district Selimbau in the form of accommodation. This research aims to know the social relations form of cooperation and accommodation on honeybee farmers in Batu Rawan Selimbau district. The method used is a qualitative method with a descriptive analysis. Data collection tools are using observation guidelines, interview guidelines, and documentation tools. The results of this research are first Social relations form of cooperation on forest honeybee farmer, seen at the father of Sarip and Hermansyah in implementing social relations form of cooperation that is to cooperate in contract and work Equally traditional. Second social relations in the form of accommodation on the forest honeybee farmer, seen in the Father Jakaria, Abang Diham, and Sukardi in implementing social relations form the accommodation is being compromises, arbitrage and tolerance. Keywords: Social Relations, Bee Farmers, Cooperation and Accommodation